КИЧИК МАКТАБ ЁШИДАГИ БОЛАЛАРНИНГ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Даўлетмуратова, Э.; Ильясова, З.; Онгарбаева, М. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of developing psychological peculiarities of pupils of primary classes. The author pays a particular attention to the individual approach to the upbringing of pupils and its influence on the collective education of young learners. The individual approach to every child among his/her classmates makes it possible to educate in him self - consciousness, striving for the purpose and a sense of citizenship.
Keywords: mind; logic memory; attraction; sympathy; truthfulness